Caspase-8 but not caspase-7 influences inflammasome activation to act in control of Brucella abortus infection - Santos, Raiany A.; Cerqueira, Daiane M.; Zamboni, Dario S.; Oliveira, Sergio C. (Frontiers in Microbiology, 2022)
Programmed cell death (PCD) is an important mechanism of innate immunity against bacterial pathogens. The innate immune PCD pathway involves the molecules caspase-7 and caspase-8, among others. Brucella abortus is a gram-negative bacterium that causes a zoonotic disease termed brucellosis. The innate immune response against this pathogen involves activation of inflammasome components and induction of pyroptosis. However, no studies so far have revealed the role of caspase-7 or caspase-8 during this bacterial infection. Herein, we demonstrate that caspase-7 is dispensable for caspase-1 processing, IL-1β secretion and cell death in macrophages. Additionally, caspase-7 deficient animals control B. abortus infection as well as the wild type mice. Furthermore, we addressed the role of caspase-8 in inflammasome activation and pyroptosis during this bacterial infection. Macrophages deficient in caspase-8 secreted reduced amounts of IL-1β that parallels with diminished caspase-1 activity when compared to wild type cells. Additionally, caspase-8 KO macrophages showed reduced LDH release when compared to wild type, suggesting that caspase-8 may play an important role in pyroptosis in response to B. abortus. Finally, caspase-8 KO animals were more susceptible to Brucella infection when compared to wild type mice. Overall, this study contributes to a better understanding of the involvement of caspase-7 and caspase-8 in innate immunity against B. abortus infection.